The impact of learning styles on attitudes to interprofessional learning among nursing students: a longitudinal mixed methods study - Susanne Lundell Rudberg; Hanna Lachmann; Taina Sormunen; Max Scheja; Margareta Westerbotn (BMC, 2023)
Abstract Background A functional interprofessional teamwork improves collaborative patient-centred care. Participation in interprofessional education promotes cooperation after graduation. Individuals tend to use different approaches to learning depending on their individual preferences. The purpose of this study was to explore nursing students' experiences of professional development with a focus on the relationship between attitudes to interprofessional learning and learning styles. Methods A longitudinal parallel mixed-methods design. The study was carried out at a Swedish three-year nursing program from August 2015 to January 2020. On enrolment, thirty-four students self-assessed their attitudes to interprofessional learning according to the Readiness for Interprofessional Learning Scale, and their learning style according to Kolbs' Learning Style Inventory. In the final semester the students participated in an interview focusing on their experiences and perceptions of teamwork and they self-assessed their attitudes to interprofessional learning again. Results Our findings indicated that 64.7% had a predominantly concrete learning style and 35.3% had a predominantly reflective learning style. No significant relationship with internal consistency reliability was identified among the participants between attitudes to interprofessional learning and learning styles. The content analysis resulted in four main categories: Amazing when it's functional; Deepened insight of care; Increased quality of care; Understanding own profession which were summarized in the theme: Well-functioning teams improve patients' outcome and working environment. Conclusion The students' attitudes to interprofessional learning were positive and it was considered as an opportunity to participate in interprofessional cooperation during internship. Transformative learning is a useful strategy in fostering interprofessional relationships due to the interdependence of various professions in interprofessional teams. When students are guided to use reflection to develop new perspectives and meaning structures, they acquire emotional and rational skills beneficial for interprofessional cooperation.